Character Building through the Scout Extracurricular Program - Tyas, Veronica; Elianasari, Elianasari; Zulaikha, Siti (International Journal of Elementary Education, 2021)
One extracurricular activity that can shape the character of students for discipline, independence, responsible, has a nationalist spirit and has social attitude and self-skill is Scout activities. This study aims to describe the implementation of scout extracurricular programs by analyzing student reactions to the implementation of scout activities, analyzing the program, and the final achievement of the Scout Extracurricular Education Program. This type of this research is evaluation research with the CIPP model (context, input, process, and product). The research method uses a combination of quantitative methods and qualitative methods (Mix Method). The purposive sampling technique is used for sampling. The source of information in this study was the principal, guide teacher, and students in classes V and VI who were actively involved in scout extracurricular activities. Data collection techniques are carried out through interviews, documentation studies, and observation. Data is taken qualitatively, then analyzed descriptively to describe the implementation of scout extracurricular programs. The results showed that scout activities carried out by character buildings followed the expected goals and results, including students being more active in learning, more patient, more focused, more sensitive, more appreciating friendship, and saving a life.